2010
DOI: 10.1063/1.3539781
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature plastic deformation of AZ31 magnesium alloy with different microstructures

Abstract: The plastic deformation of AZ31 magnesium alloy under tension at temperatures of 4.2–295K is studied as a function of its microstructure following squeeze casting (SC) and after severe plastic deformation (SPD) by hot rolling and equal-channel angular pressing. SPD reduces the average grain size and creates a texture that favors basal-plane dislocation glide. It is found that plastic deformation becomes unstable (serrated) at temperatures of 4.2–25K and more stress jerks occur in the SPD polycrystal than in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The CRSS values of prismatic and pyramidal slips are as high as 40 MPa or more 18 , but it decreases significantly with increasing temperature. In Mg alloys {10 1}, the CRSS required for compression twins is 76–153 MPa 19 , which is much greater than the CRSS (2–3 MPa) required for {10 2} tensile twins 20 , 21 . In conclusion, the above reasons can also explain that 86° <11 0> tensile twins are more likely to appear during ultra-low temperature rolling.…”
Section: Resultsmentioning
confidence: 97%
“…The CRSS values of prismatic and pyramidal slips are as high as 40 MPa or more 18 , but it decreases significantly with increasing temperature. In Mg alloys {10 1}, the CRSS required for compression twins is 76–153 MPa 19 , which is much greater than the CRSS (2–3 MPa) required for {10 2} tensile twins 20 , 21 . In conclusion, the above reasons can also explain that 86° <11 0> tensile twins are more likely to appear during ultra-low temperature rolling.…”
Section: Resultsmentioning
confidence: 97%
“…78 Small grains have a higher resistance to crack propagation due to strain distribution between grain boundaries. 79,80 The fracture mode for Exp. 2 shows a high ductility and lower UTS indicated by lower and deeper dimples, whereas larger and shallow dimples for Exp.…”
Section: Resultsmentioning
confidence: 99%
“…Bagheri et al 56 noted that grain boundaries reduce the growth of cracks within the microstructure and postpone the fracture, which results in an increase in ductility. Estrin et al 57 found that intergranular fracture transforms to transgranular fracture as grain size decreases and ductility increases as grain size decreases. Das et al 58 also indicated that as grain size reduces, the density of geometrically necessary dislocations, which accommodated the strain among the grains increases, and ductility increases.…”
Section: Mechanical Analysismentioning
confidence: 99%